2022
DOI: 10.15174/au.2022.3489
|View full text |Cite
|
Sign up to set email alerts
|

Caracterización fisicoquímica de material particulado del Popocatépetl, trayecto Atlixco-Puebla, y su impacto en la salud y el ambiente

Abstract: El estudio determinó la presencia de material particulado (MP) emitido por el volcán Popocatépetl los días 29 y 31 de marzo de 2019 en el trayecto Atlixco-Puebla. El objetivo fue identificar tamaño y naturaleza química del MP en esta zona y reconocer el impacto en la salud (por inhalación) y el ambiente, así como comparar las cenizas de los años 1994, 2012 y 2019. El MP suspendido se cuantificó con un contador DT-9880, los metales totales y lixiviados se calcularon por espectrofotometría de absorción atómica (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Indicating an enrichment of this non-soluble compound in the second extraction season. On the other hand, concerning the obtained ash it can be observed that the bands from 3350 cm -1 to 1632 cm -1 disappear and bands appear around 1425 cm -1 with higher intensity associated to the deformation of methyl CH3 and CH2 and the Si-H vibration of the Si-CH3 group [12,13], as well as the appearance of the band near 1024 cm -1 exactly at 1037 cm -1 associated to the silicates [13]. In the second extraction these bands are more intense, it is associated to a higher content of minerals in the water bodies and therefore in the ash obtained in that extraction season, the presence of minerals in the lagoons favors the propagation of emergent macrophytes such as Tule and Water Lily, contributing to the eutrophication of the lagoons.…”
Section: Ftir Analysismentioning
confidence: 93%
“…Indicating an enrichment of this non-soluble compound in the second extraction season. On the other hand, concerning the obtained ash it can be observed that the bands from 3350 cm -1 to 1632 cm -1 disappear and bands appear around 1425 cm -1 with higher intensity associated to the deformation of methyl CH3 and CH2 and the Si-H vibration of the Si-CH3 group [12,13], as well as the appearance of the band near 1024 cm -1 exactly at 1037 cm -1 associated to the silicates [13]. In the second extraction these bands are more intense, it is associated to a higher content of minerals in the water bodies and therefore in the ash obtained in that extraction season, the presence of minerals in the lagoons favors the propagation of emergent macrophytes such as Tule and Water Lily, contributing to the eutrophication of the lagoons.…”
Section: Ftir Analysismentioning
confidence: 93%